Time perception and age - Ferreira, Vanessa Fernanda Moreira; Paiva, Gabriel Pina; Prando, Natália; Graça, Carla Renata; Kouyoumdjian, João Aris (Arquivos de Neuro-Psiquiatria, 2016)
Our internal clock system is predominantly dopaminergic, but memory is predominantly cholinergic. Here, we examined the common sensibility encapsulated in the statement: “time goes faster as we get older”.Objective To measure a 2 min time interval, counted mentally in subjects of different age groups.Method 233 healthy subjects (129 women) were divided into three age groups: G1, 15-29 years; G2, 30-49 years; and G3, 50-89 years. Subjects were asked to close their eyes and mentally count the passing of 120 s.Results The elapsed times were: G1, mean = 114.9 ± 35 s; G2, mean = 96.0 ± 34.3 s; G3, mean = 86.6 ± 34.9 s. The ANOVA-Bonferroni multiple comparison test showed that G3 and G1 results were significantly different (P < 0.001).Conclusion Mental calculations of 120 s were shortened by an average of 24.6% (28.3 s) in individuals over age 50 years compared to individuals under age 30 years.
Keywords: time perception; age; timing; aging